Ecology of Problem Individuals and the Efficacy of Selective Wildlife Management. (July 2017) - Swan, George J.F.; Redpath, Steve M.; Bearhop, Stuart; McDonald, Robbie A.
Abstract : As a result of ecological and social drivers, the management of problems caused by wildlife is becoming more selective, often targeting specific animals. Narrowing the sights of management relies upon the ecology of certain 'problem individuals' and their disproportionate contribution to impacts upon human interests. We assess the ecological evidence for problem individuals and confirm that some individuals or classes can be both disproportionately responsible and more likely to reoffend. The benefits of management can sometimes be short-lived, and selective management can affect tolerance of wildlife for better or worse, but, when effectively targeted, selective management can bring benefits by mitigating impact and conflict, often in a more socially acceptable way. Trends: In response to ecological and social drivers, there is a trend towards selective wildlife management that targets the individual rather than the population. The move towards selectivity in wildlife management is running in parallel with growing recognition of the prevalence and importance of intraspecific variation in ecology and evolution. As well as being logistically challenging, removing 'problem individuals' may inadvertently apply selective pressures on correlated traits (such as sex, size, or social position) that could have indirect, negative impacts on populations. Social perspectives on ecological outcomes of selective management highlight the importance of interdisciplinary research integrating ecological and social dynamics.